unicwaan
  • unicwaan
Use mathematical induction to prove the statement is true for all positive integers n, or show why it is false.
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
unicwaan
  • unicwaan
\[1^2+4^2+7^2+...+(3n−2)^2=\frac{ n(6n2−3n−1) }{ 2 }\]
mathstudent55
  • mathstudent55
An induction proof works like this: 1. Show the formula works for n = 1 2. Assume it works for n = k 3. Show it works for n = k + 1
mathstudent55
  • mathstudent55
Let's start. Can you show the formula works for n = 1? Copy the formula. Then rewrite the formula replacing n with 1. What do you get?

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

mathstudent55
  • mathstudent55
\(\Large 1^2+4^2+7^2+...+(3n−2)^2=\dfrac{ n(6n2−3n−1) }{ 2 }\) Let n = 1 \(\Large [3(1)−2)]^2=\dfrac{ 1(6 \cdot 1^22−3 \cdot 1−1) }{ 2 }\) \(\Large 1 = \dfrac{1(2)}{2} \) \(\Large 1 = 1\) We proved the expression works for n = 1.
mathstudent55
  • mathstudent55
Now we assume the expression is true for n = k: \(\Large 1^2 + 4^2 + 7^2 + ... + (3k - 2)^2 = \dfrac{k(6k^2 - 3k - 1)}{2} \)
mathstudent55
  • mathstudent55
Now we need o prove it works for n = k + 1 \(\Large 1^2 + 4^2 + 7^2 + ...+ (3k - 2)^2 + [3(k + 1) - 2]^2 =\) \(\Large = \dfrac{(k + 1) [6(k + 1)^2 - 3(k + 1) - 1]}{2} \) \(\Large = \dfrac{(k + 1)[6(k^2 + 2k + 1) - 3k -3 - 1]}{2} \) \(\Large = \dfrac{(k + 1)(6k^2 + 12k + 6 - 3k - 4)}{2} \) \(\Large = \dfrac{(k + 1)[6(k^2 + 2k + 1) - 3k - 3 - 1)}{2} \) \(\Large = \dfrac{(k + 1)[6(k + 1)^2 - 3(k + 1) - 1)}{2} \) The last expression above is the formula with k replaced by k + 1. This shows the formula works for n = k + 1. By induction, the formula has been proved to be true.
madhu.mukherjee.946
  • madhu.mukherjee.946
@mathstudent55 superb
mathstudent55
  • mathstudent55
@madhu.mukherjee.946 Thanks!
unicwaan
  • unicwaan
Thank you for showing me the walk-through steps! Sorry that I went away from my compute! @mathstudent55

Looking for something else?

Not the answer you are looking for? Search for more explanations.